The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/polym14173612
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Catalytic Property Studies for Isoprene Polymerization of Iron Complexes Bearing Unionized Pyridine-Oxime Ligands

Abstract: Iron complexes of the types [Fe(HL)2Cl2] (Fe1: HL1 = pyridine-2-aldoxime; Fe2: HL2 = 6-methylpyridine-2-aldoxime; Fe3: HL3 = phenyl-2-pyridylketoxime; Fe4: HL4 = picolinaldehyde O-methyl oxime) were prepared and characterized by elemental analysis and IR spectroscopy. The crystal structure of Fe2, determined by single-crystal X-ray diffraction, featured a distorted octahedral coordination of the iron center binding with two ligands of HL2. The X-ray structure and infrared spectral data indicated that pyridine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Moreover, the N oxime atoms of each ligand have a stronger coordination than N pyridine at the cobalt center according to the bond lengths [Co-N1 = 2.188 (17), Co-N2 = 2.098 (16), Co-N3 = 2.219 (16), Co-N4 = 2.132 (16)]. Consistent with the previous work of pyridine-oxime iron complex [65], the oxime proton is unionized. (15).…”
Section: Synthesis and Characterization Of Co(ii) Complexessupporting
confidence: 86%
See 3 more Smart Citations
“…Moreover, the N oxime atoms of each ligand have a stronger coordination than N pyridine at the cobalt center according to the bond lengths [Co-N1 = 2.188 (17), Co-N2 = 2.098 (16), Co-N3 = 2.219 (16), Co-N4 = 2.132 (16)]. Consistent with the previous work of pyridine-oxime iron complex [65], the oxime proton is unionized. (15).…”
Section: Synthesis and Characterization Of Co(ii) Complexessupporting
confidence: 86%
“…2). However, it needs to be emphasized that the pyridine-oxime ligated iron complex bearing one 6-methyl substituent at pyridine ring showed lower activity because of steric hindrance in the previous work [65]. Zhang's group also reported that the substituent at the 6-position of the pyridine ring significantly influenced the catalytic performances of the iminopyridine ligated Co complexes.…”
Section: Polymerization Of Isoprene Catalyzed By Co(ii) Complexesmentioning
confidence: 94%
See 2 more Smart Citations
“…In 2018, Gong’s group demonstrated that cis -1,4- alt -3,4 polyisoprene can be achieved with aminophosphine(ory)-fused bipyridine-based cobalt complexes in combination with MMAO [ 3 ]. Subsequently, Wang and coworkers investigated the effect of fluorine substituents on isoprene polymerization catalyzed by iminopyridine-supported cobalt catalysts activated by AlEt 2 Cl or MAO/[Ph 3 C][B(C 6 F 5 ) 4 ] [ 32 , 33 , 34 ]. The binary system exhibited high catalytic activity and cis -1,4 selectivity, and also obtained high-molecular-weight polyisoprene.…”
Section: Introductionmentioning
confidence: 99%